Transformasi Santri Go Internasional dan Islami Pesantren di Masa Depan - Ainun Najib; Ahmad Zaini (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
It is time for santri and Islamic boarding schools to transform, considering the increasingly rapid development, both at the level of knowledge and experience. Students must be aware of knowledge and experience (soft skills and hard skills), especially nowadays, competition in the national and even international realm provides various kinds of knowledge. In this case, scientific knowledge (science and technology) must be studied by Santri, not just religious knowledge. Therefore, Islamic boarding schools must have long-term programs, where the program has the output that Islamic boarding schools can become universities, or at least be on par with universities. This paper is based on a library research study with an epistemological-positivistic approach. The focus of the problem in this paper is, How do Santri and Islamic Boarding Schools transform? The conclusion is that students with their self-concept will improve their soft skills and hard skills. So that the Islamic Boarding School's ideals will be realized even though it goes through many processes. Future Islamic boarding schools must have long-term programs, so that they are the same as university level.